Adverse effect of sildenafil on healing ischemic wounds: Results of an in vivo study - (:unkn) unknown (HMP Communications, 2015)
Phosphodiesterase-5 is an enzyme that inactivates cyclic guanosine monophosphate and regulates the balance of nitric oxide (NO). NO is an important molecule synthesized during wound repair. An in vivo study was conducted to evaluate the effect of sildenafil, known to have a role in regulating the effect of NO in perfusion, on the wound healing process under ischemic conditions in rats. Reepithelialization, neovascularization, inflammatory cells, and amount and maturation of granulation tissue were scored on a scale of 0-3 (none, partial, complete but immature/thin, complete and mature, respectively). Data were analyzed using ANOVA one-way test, with statistical significance determined at P <0.05. Fortytwo (42) Sprague-Dawley rats were anesthetized, wounded with H-shaped flaps, and randomized into 2 groups: 1 group received 10 mg/kg sildenafil (dissolved in 1 mL distilled water) orally via orogastric tubes and the other group received a 0.9% NaCl solution via intraperitoneal injection (0.1 mL). On days 3, 5, and 10, 7 rats from each group were sacrificed. Blinded investigators analyzed skin samples for the wound healing evaluating criteria using from hematoxylin/eosin staining under an optical microscope at 10x and 40x magnification. Histopathological analysis showed sildenafil significantly reduced reepithelialization, neovascularization, amount of granulation tissue, and number of inflammatory cells on day 3 and increased inflammatory cells on day 10 (P <0.05). Further research is needed to clarify the potential role of oral or topically applied different doses of sildenafil for ischemic wound healing as well to evaluate its safety and efficacy when administered alone or in combination with other therapies.
Keywords: Animal models; Ischemia; Sildenafil; Wound healing